Can I Get a Witness? Miriam’s Song in the Literary Design of Exodus - Imes, Carmen Joy 1977- (2023)
Miriam plays a disproportionate role in the literary design of Exodus because she strategically participates in both major rescue operations. She witnesses the rescue of her brother Moses as well as the rescue of the Israelite nation from Pharaoh’s oppressive regime in Egypt. The stories about her in Exodus provide a frame for these acts of deliverance. Her song also functions prophetically; as the sister of Aaron, she, too, functions as Moses’s spokesperson and calls upon Israel to respond faithfully. This article counters current scholarship (R. Burns and R. Hawkins) by providing a better explanation of Miriam’s namelessness in chapter 2 and her prophetic activity in chapter 15. It engages with G. Janzen’s assessment that the song of Miriam is analeptic, occurring before Moses’s longer version of the song. Her rebellion story in Num 12 and the prophet Micah’s recognition of her leadership role alongside Moses and Aaron both suggest that Miriam was highly revered and deeply loved. Literarily, she bears witness to God’s saving work and calls upon readers to respond in celebration.
Keywords: Aaron; Exodus; Miriam; Moses; "Exodus 15:20–21"; "Exodus 2:1–10"; "Hebrew Bible prophecy"; "literary design of Exodus"; "women prophets"